(untitled) (Economic and Political Thought, 2020)
The article refers to the issue of transformation of the 1990s in Central and Eastern Europe in the face of the problem of implication of the assumptions of the social market economy. The first part of the article compares the paradigms of Keynesian economics, neoliberal economics and social market economy. This part discusses the main assumptions of these trends, their differences and similarities as well as the consequences they have brought to economic systems. In the next part the authors present the problem of the Washington Consensus and the changes introduced to the Polish economy. The discussed content aims to indicate the difficulty of implementing classic principles of the social market economy in Poland.The aim of the article is to verify the thesis that social enterprises can be an alternative to the systemic market economy. In the article, social enterprises were defined as entities that are locally rooted, and are part of the process of endogenous local development.